Social Salience Discriminates Learnability of Contextual Cues in an Artificial Language - Rácz, Péter; Hay, Jennifer B.; Pierrehumbert, Janet B. (Frontiers in Psychology, 2017)
We investigate the learning of contextual meaning by adults in an artificial language. Contextual meaning here refers to the non-denotative contextual information that speakers attach to a linguistic construction. Through a series of short games, played online, we test how well adults can learn different contextual meanings for a word-formation pattern in an artificial language. We look at whether learning contextual meanings depends on the social salience of the context, whether our players interpret these contexts generally, and whether the learned meaning is generalised to new words. Our results show that adults are capable of learning contextual meaning if the context is socially salient, coherent, and interpretable. Once a contextual meaning is recognised, it is readily generalised to related forms and contexts.